Map-Based Cloning of Seed Dormancy1-2 Identified a Gibberellin Synthesis Gene Regulating the Development of Endosperm-Imposed Dormancy in Rice. Issue 3 (15th September 2015) - Ye, Heng; Feng, Jiuhuan; Zhang, Lihua; Zhang, Jinfeng; Mispan, Muhamad S.; Cao, Zhuanqin; Beighley, Donn H.; Yang, Jianchang; Gu, Xing-You
Abstract : Natural variants in a gibberelin synthesis gene affect the development of primary dormancy by regulating seed morphogenesis and maturation programs to influence germination capability at harvest. Abstract: Natural variation in seed dormancy is controlled by multiple genes mapped as quantitative trait loci in major crop or model plants. This research aimed to clone and characterize the Seed Dormancy1-2 ( qSD1-2 ) locus associated with endosperm-imposed dormancy and plant height in rice ( Oryza sativa ). qSD1-2 was delimited to a 20-kb region, which contains OsGA20ox2 and had an additive effect on germination. Naturally occurring or induced loss-of-function mutations of the gibberellin (GA) synthesis gene enhanced seed dormancy and also reduced plant height. Expression of this gene in seeds (including endospermic cells) during early development increased GA accumulation to promote tissue morphogenesis and maturation programs. The mutant allele prevalent in semidwarf cultivars reduced the seed GA content by up to 2-fold at the early stage, which decelerated tissue morphogenesis including endosperm cell differentiation, delayed abscisic acid accumulation by a shift in the temporal distribution pattern, and postponed dehydration, physiological maturity, and germinability development. As the endosperm of developing seeds dominates the moisture equilibrium and desiccation status of the embryo in cereal crops, qSD1-2 is proposed to control primary dormancy by a GA-regulated dehydration mechanism. Allelic distribution of OsGA20ox2, the rice Green Revolution gene, was associated with the indica and japonica subspeciation. However, this research provided no evidence that the primitive indica- and common japonica- specific alleles at the presumably domestication-related locus functionally differentiate in plant height and seed dormancy. Thus, the evolutionary mechanism of this agriculturally important gene remains open for discussion.